2019
DOI: 10.3389/fmicb.2019.02328
|View full text |Cite
|
Sign up to set email alerts
|

Gymnemic Acids Inhibit Adhesive Nanofibrillar Mediated Streptococcus gordonii–Candida albicans Mono-Species and Dual-Species Biofilms

Abstract: Dental caries and periodontitis are the most common oral disease of all age groups, affecting billions of people worldwide. These oral diseases are mostly associated with microbial biofilms in the oral cavity. Streptococcus gordonii, an early tooth colonizing bacterium and Candida albicans, an opportunistic pathogenic fungus, are the two abundant oral microbes that form mixed biofilms with augmented virulence, affecting oral health negatively. Understanding the molecular mechanisms of the pathogen interactions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Interestingly, a study by Wan and co-workers (2021) found that the binding force between C. albicans and S. gordonii is approximately 2-fold higher than that between C. albicans and S. mutans. These interactions may also depend on the enhanced production of EXM by PMB (Montelongo-Jauregui et al, 2019) and specific nanostructures, such as C. albicans-produced nanofibrils (Veerapandian and Vediyappan, 2019).…”
Section: Regulation Of the Complex Interactionmentioning
confidence: 99%
“…Interestingly, a study by Wan and co-workers (2021) found that the binding force between C. albicans and S. gordonii is approximately 2-fold higher than that between C. albicans and S. mutans. These interactions may also depend on the enhanced production of EXM by PMB (Montelongo-Jauregui et al, 2019) and specific nanostructures, such as C. albicans-produced nanofibrils (Veerapandian and Vediyappan, 2019).…”
Section: Regulation Of the Complex Interactionmentioning
confidence: 99%
“…It decreases the amount of e-DNA present in biofilm. It also inhibits the adhesive property of C. albicans by inhibiting an enzyme glyceraldehyde-3-phosphate dehydrogenase, which is thought to be responsible for the display of adhesion property in C. albicans (Veerapandian and Vediyappan, 2019). Similarly, Waikiloid A 131a prenylated indole alkaloid and polyketide metabolite Waikialide A132 obtained from a Hawaiian Aspergillus spp.…”
Section: Natural Extracts and Essential Oilsmentioning
confidence: 99%
“…Out of 20 fractions of G. sylvestre extract obtained from Rotofor IEF, the dark-colored molecules (terpenoid saponins) were migrated and enriched at the anode end (pH 2-3) and the light-yellow clear fractions were observed at cathode end (pH 8-9) ( Figure 2). Aliquots (20 l) from each fraction (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were separated after reducing and boiling on 15% SDS-PAGE. The Coomassie bluestained gel shows the diffused polypeptide band of about 5 kDa that is enriched in fractions 16-19 ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%